Rapid diagnosis of avian infectious bronchitis virus by the polymerase chain reaction - Falcone, Emiliana (J Virol Methods, 1997)
A simple, sensitive and specific polymerase chain reaction (PCR) procedure was developed in order to detect infectious bronchitis virus (IBV) directly in tissue samples. Viral RNA was extracted from allantoic fluids and cell cultures infected experimentally with different strains of IBV and from tissues of naturally infected birds. Viral RNA was then amplified and identified by a nested RT-PCR assay using two sets of primers flanking a well-conserved region of the nucleocapsid gene. The selected IBV nucleocapsid sequence was detected successfully by simple direct electrophoresis of amplified material.